Pengaruh Penerapan Metode Pembiasaan Terhadap Pembentukan Sikap Perilaku Siswa Kelas VIII di MTs Jatibogor Tegal - Atika Rohadatul Aisyi (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2023)
Advances in science and technology are accelerating, making competition in human resources very competitive. In this case, school is the basic level of education that is expected to be a strong foundation for shaping students' attitudes and behavior. Along with the times, the function of the school environment has many challenges. Efforts in shaping attitudes, behavior and personality can be done through habituation, in this case MTs Jatibogor Tegal has implemented several habituation programs implemented by school community. habituation method is one of the methods used as a benchmark in the formation of student attitudes and behavior. This research method is descriptive research using a quantitative approach. The population in this study was 190 students, the sample used was 48 students. Data collection techniques using questionnaire instruments and observation instruments. The data were analyzed using the product moment correlation method by presenting the data and drawing conclusions. Based on the results of the test analysis of product moment correlation analysis shows that the value of r_count> r_table is 0.455> 0.288, meaning that there is a positive correlation between the application of the habituation method to the formation of behavioral attitudes of class VIII students at MTs Jatibogor Tegal. Because the correlation value is located at 0.40 - 0.70, then there is a moderate relationship between the variable application of habituation methods with the formation of behavioral attitudes of 8th grade students at MTs Jatibogor Tegal. With this it is stated that there is an influence between the application of habituation methods on the formation of behavioral attitudes of class VIII students at MTs Jatibogor. While the amount of influence is 20.7%, while 79.3% is influenced by other factors.